Measuring Efficiency Of Commercial Banks In The Gambia - Jaabi, Seeku; Fatty, Babucar Malang (Advances in Social Sciences Research Journal, 2018)
The long-term sustainability of commercial banks depend largely on how efficiently they are managed. This study explores the relative efficiency of commercial banks in the Gambia, by examining the banks’ operational characteristics on efficiency measures. The study critically examines the efficiency levels of seven commercial banks (six conventional banks and one Islamic bank) in The Gambia from 2005 to 2009 using the Data Envelopment Analysis (DEA) methodology to examine selected banks’ relative efficiency levels. Also, using Tobit regression model, the study examines the relationship between banks’ specific characteristics (i.e banks size, profitability and market power) and efficiency measures - Technical Efficiency (TE), Pure Technical Efficiency (PTE) and Scale Efficiency (SE). The results from DEA exhibit that the majority of Gambian banks are fully efficient under the assumption of VRS. The findings showed that Trust Bank Ltd (TBL) was the most efficient bank while International Commercial Bank (ICB), the least efficient bank during the period. The results of Tobit Regression Model showed only bank size is significantly and positively related to TE and SE, while both profitability and market power were negatively associated with TE and SE, indicating no relationship between profitability and market power with efficiency measures in Gambian banking industry.